Maxillary expander with differential opening versus fan-type expander: a randomized clinical trial - Massaro, Camila da Silveira (2020)
Introduction: The aim of this two-arm parallel randomized clinical trial was to compare the dentoskeletal effects of the expander with differential opening (EDO) and the fantype expander (FE) in the mixed dentition by means of cone-beam computed tomography (CBCT) and digital dental models. Methods: A sample of 48 patients were randomly allocated into 2 study groups. Group EDO comprised 24 patients (13 female, 11 male; mean age of 7.62 years) treated with the expansion with differential opening. Group FE was composed by 24 patients (14 female, 10 male; mean age of 7.83 years) treated with the fan-type expansion. CBCT scans and digital dental models were acquired before treatment and after rapid maxillary expansion. Maxillary threedimensional (3D) dentoskeletal changes were assessed in 3D models derived from CBCT scans superimposed on the cranial base using the software ITK-SNAP and 3D Slicer. Changes in the maxillary interincisal diastema and maxillary and mandibular arch width, arch perimeter, arch length, arch size and arch shape were assessed in digital dental models using the software OrthoAnalyzer, Stratovan Checkpoint and MorphoJ. Intra-rater reliability was tested with Intraclass Correlation Coefficient. Intergroup comparisons were performed using t or Mann-Whitney U tests with Holm- Bonferroni correction (P<0.05). Results: The EDO group showed greater maxillary skeletal lateral displacements, while the vertical and anteroposterior changes were similar in both groups. The increase in the intercanine distance and the canine buccal inclination were greater in the FE group, while the intermolar changes and the molar buccal inclination were greater in the EDO group. Both groups demonstrated similar increases in the maxillary interincisal diastema width and similar changes were observed in the maxillary and mandibular arch length and arch perimeter. Changes in the mandibular arch width were mild and similar in both groups, except for the interfirst permanent molars distance that showed a slight greater increase in the EDO group. Maxillary arch shape changed significantly for both differential and fan-type expanders. The posttreatment arch shape was larger in the anterior region for patients treated with the FE and larger in the posterior region for patients treated with EDO. Conclusions: In the mixed dentition, the EDO produced a greater transversal skeletal expansion compared to the FE, with similar vertical and anteroposterior effects. Dental changes were greater in the molar region for patients treated with EDO and in the canine region for patients treated with FE. Maxillary arch shape changes were distinct between EDO and FE. A slightly greater mandibular spontaneous expansion was observed for EDO only at the first molar region.